Comparison of dexamethasone regimens in tubercular meningitis (TBM): a randomized open label clinical trial - Alvee Saluja; Deepti Vibha; Awadh Kishor Pandit; Garima Shukla; Achal Kumar Srivastava; Manjari Tripathi; Madakasira Vasantha Padma Srivastava; Kameshwar Prasad; Sada Nand Dwivedi (Journal of Infection in Developing Countries)
Introduction: Corticosteroids are used as adjunctive treatment in tuberculous meningitis (TBM). However, there is no universally accepted regimen, type, duration, or route of steroid administration.